2009
DOI: 10.1002/ana.21602
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Parkison's disease: Tools to assess Parkinson's disease onset and progression

Abstract: Reliable and well-validated biomarkers for PD to identify individuals "at risk" before motor symptoms, accurately diagnose individuals at the threshold of clinical PD, and monitor PD progression throughout its course would dramatically accelerate research into both PD cause and therapeutics. Biomarkers offer the potential to provide a window onto disease mechanism, potentially generating therapeutic targets for disease. In particular, biomarkers enable investigation of the premotor period of PD before typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 117 publications
(97 reference statements)
0
35
0
Order By: Relevance
“…These reports indicate the difficulty of making a precise evaluation of possible PD cases based solely on clinical data. In contrast, depicting abnormalities of the dopamine system on a molecular basis has a greater advantage (6,(20)(21)(22)(23)(24)(25). Previous studies showed that the progression of PD was associated with a similar rate of dopaminergic losses in all striatal subregions (26).…”
Section: Discussionmentioning
confidence: 99%
“…These reports indicate the difficulty of making a precise evaluation of possible PD cases based solely on clinical data. In contrast, depicting abnormalities of the dopamine system on a molecular basis has a greater advantage (6,(20)(21)(22)(23)(24)(25). Previous studies showed that the progression of PD was associated with a similar rate of dopaminergic losses in all striatal subregions (26).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical severity corresponding to the Kurlan score at the end of the rapid progress stage in this study may represent the initial level of damage to the dopaminergic system induced by MPTP. The score of the monkey manifesting spontaneous recovery was 14 at the end of rapid progress stage, much lower than that of the other animals (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Studies have suggested that stable Parkinsonism occurs in severe cases despite varying degrees of response to MPTP treatment [20].…”
Section: Discussionmentioning
confidence: 93%
“…Clinical symptoms appear when 50%-60% of dopaminergic neurons and [70%-80% of striatal nerve terminals have degenerated or died. The concept of a clinical symptom threshold is based on data derived from decreased dopamine levels in post-mortem tissue from humans and altered dopaminergic function observed in radioisotopic brain imaging [26,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicopathological studies from the UK and Canada have shown that the disease is diagnosed incorrectly in about 25 % of patients [48]. The pre-motor period before diagnosis may be long (5-20 years) and at the time of the diagnosis already 50-60 % of the dopaminergic neurons may be lost [22,38].…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%